Motivation and Compensation on Employee Performance - Hastuti Mulang (Advances in Human Resource Management Research, 2022)
This research was conducted aiming to find out how the motivation and compensation received by employees, as well as to determine the effects of motivation and compensation on employee performance at PT. Hadji Kalla Branch Urip Sumoharjo. In this study, the population is all employees of PT. Hadji Kalla of Urip Sumoharjo Branch numbered 190 people. Researchers used several data collection techniques, namely questionnaires, observation, document review and interviews. The types of data used in this study consisted of quantitative data and qualitative data. The source of this research data is primary data, namely data directly obtained from data sources or research subjects. The data obtained using descriptive statistical analysis method, inferential statistical analysis. Descriptive statistical analysis used in this research is descriptive analysis, namely the analysis that suggests about the respondent's personal data, which was obtained from the respondents' answers through questionnaires. The result of this research is the motivation variable has a significant influence on the performance of the employees of PT. Hadji Kalla Branch Urip Sumoharjo and compensation variables have a significant influence on the performance of employees of PT. Hadji Kalla Branch Urip Sumoharjo.